The Effect of Financial Crises on Growth and FDI in some African Countries: A Panel VECM Approach - Oche, Mary O.; Khamfula, Yohane; Mah, Gisele (Journal of Reviews on Global Economics, 2019)
This study investigates the effects of financial crises on economic growth and foreign direct investment in some African countries. A panel vector error correction model is used for the analysis of annual time series data for the period 1994 to 2014. From economic growth model, in the long run, it is observed that gross domestic product per capita is positively influenced by investment, trade and foreign direct investment; with investment and trade being statistically significant. Gross domestic product per capita has a negative significant relationship with real effective exchange rate. On the other hand, in the long run, the investment model shows that investment has a significant positive relationship with both gross domestic product per capita and investment; while it has a negative significant relationship with real effective exchange rate and trade. Also observed from the results is that financial crisis has a negative relationship with both economic growth and foreign direct investment. This study recommends more openness of the economy so as to promote both economic growth and inflow of foreign direct investment in countries. It also recommends the need to encourage more gross fixed capital formation in order to promote both economic growth and foreign direct investment.